Electrostatic screening and Friedel oscillations in semiconducting nanotubes: Carbon nanotubes, quantum wires and Luttinger liquid - Chaplik, A.V.; Magarill, L.I.; Vitlina, R.Z. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
In 3D and 2D electronic systems the singular contribution to the static permittivity ε (Kohn singularity) is a small correction to the regular part of ε but it results in the leading term in asymptotic behavior of the screened potential (Friedel oscillations). In the present letter we show that for nanotubes quite different results are valid: ε becomes infinitely large at the singular point and the Friedel oscillations do not play the dominant role in the screening at the large distances. Moreover, the zero and highest cylindrical harmonics of the effective potential are screened by quite different mechanisms.